Design and implementation of embedded tracking system using spatial parallelism on FPGA for robotics / \c Noor Aldeen Abbas Khalid. - Abbas Khalid, Noor Aldeen (School of Computer and Communication Engineering, Universiti Malaysia Perlis, 2017)
Two following objectives were carried ; to develop and implement an embedded robot tracking system with the help of a spatial parallelism of FPGA ; to enhance the robot tracking system using the long-range IR and contactless temperature sensors (TMP007), and also avoid the obstacles using an ultrasonic sensor.